2021
DOI: 10.3390/cells10102718
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Tropical Plant Extracts That Extend Yeast Chronological Life Span

Abstract: Certain plant extracts (PEs) contain bioactive compounds that have antioxidant and lifespan-extending activities on organisms. These PEs play different roles in cellular processes, such as enhancing stress resistance and modulating longevity-defined signaling pathways that contribute to longevity. Here, we report the discovery of PEs that extended chronological life span (CLS) in budding yeast from a screen of 222 PEs. We identified two PEs, the leaf extracts of Manihot esculenta and Wodyetia bifurcata that ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
1
1
0
Order By: Relevance
“…The behaviour of this extract showed that the sensitivity of the extract caused inhibition in cell viability to occur at physiologically relevant concentrations (low concentrations) and increasing concentrations resulted in no further inhibition in cell viability. This effect is consistent with previous studies where similar effects have been reported [ 41 , 42 ].…”
Section: Discussionsupporting
confidence: 94%
“…The behaviour of this extract showed that the sensitivity of the extract caused inhibition in cell viability to occur at physiologically relevant concentrations (low concentrations) and increasing concentrations resulted in no further inhibition in cell viability. This effect is consistent with previous studies where similar effects have been reported [ 41 , 42 ].…”
Section: Discussionsupporting
confidence: 94%
“…Doubling times (δ) were calculated between every consecutive pair of absorbance values, by the formula: δ = , whereby A 1 and A 2 are successive absorbance values while t 1 and t 2 are the times between measurement of successive absorbance. Survival percentage of each replicate of each strain was then averaged 1 , 36 .…”
Section: Methodsmentioning
confidence: 99%
“…In the second approach, the so-called chronological aging is used as a model for studying postmitotic cells of higher eukaryotes, including humans [16,20]. Many factors are known to influence the aging of yeast, including calory restriction [21], anti-aging compounds [22][23][24], ribosome biogenesis disorders [25][26][27], mitochondrial dysfunction [28], and an increased level of reactive oxygen species, leading to oxidative damage [29] or extrachromosomal rDNA circles (ERCs) formation [30,31]. However, despite extensive research on aging, little is known about the possible linkage between replication initiation and aging.…”
Section: Introductionmentioning
confidence: 99%